2017
DOI: 10.1515/aiht-2017-68-2994
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity associated with statins

Abstract: Treatment with statins is known all over the world. They are generally considered safe at therapeutic doses. Nevertheless, clinical trials are not enough to assess their scarce adverse effects such as idiosyncratic drug induced liver injury (DILI). Due to some conditions, such as concomitant usage (drug-drug interaction using an identical metabolising enzyme) and genetic polymorphisms, there is an increasing concern about their safety. Hepatotoxicity and rhabdomyolysis have begun to appear in published studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 49 publications
(49 reference statements)
0
42
0
5
Order By: Relevance
“…The exact mechanism by which statins cause ALT elevation is not well understood and liver injury is extremely rare. Animal experiments suggest that liver toxicity is not seen at therapeutic doses, but is seen in higher doses of statins . In a study, it was aimed to determine the effects of atorvastatin therapy on ALT and AST levels in patients with type 2 diabetes and chronic hepatitis C. On the basis of the results of the study, atorvastatin was suggested to improve liver profile by decreasing ALT and AST enzyme activities in both diseases .…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism by which statins cause ALT elevation is not well understood and liver injury is extremely rare. Animal experiments suggest that liver toxicity is not seen at therapeutic doses, but is seen in higher doses of statins . In a study, it was aimed to determine the effects of atorvastatin therapy on ALT and AST levels in patients with type 2 diabetes and chronic hepatitis C. On the basis of the results of the study, atorvastatin was suggested to improve liver profile by decreasing ALT and AST enzyme activities in both diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Statins may cause hepatotoxicity by causing mitochondrial dysfunction; after treatment with statins, it causes a huge increase in mitochondrial superoxide which leads to mitochondrial impairment 24 . In a study involving 185 patients treated with statins, at clinical presentation, 57.8 % presented with a hepatocellular pattern, 18.3 % a cholestatic, and 23.2 % a mixed one 25 .…”
Section: Statinsmentioning
confidence: 99%
“…Предрасполагающими факторами к развитию как повре ждения печени, так и миопатии являются высокоинтенсивная терапия статинами, комбинированная терапия дислипидемии, сопутствующая терапия другими лекарствами, которые метаболизируются с участием цитохрома Р450, предшествующая печеночная или почечная недостаточность, пожилой возраст [54,55].…”
Section: статины и повышение трансаминазunclassified